Introductory Circuit Analysis 8th edition - Boylestad (Prentice Hall, 2012)
The most widely acclaimed introduction to circuit analysis for more than three decades, this book guides readers to a solid foundation in the basics of ac/dc circuits, specific theorems, and currently used analysis software (e.g., PSpice (Windows) Version 8, Addendum-Or CAD PSpice (Windows); BASIC MathCAD TI86 Calculator). It features exceptionally clear explanations and descriptions, step-by-step examples, and practical applications. Current and Voltage. Resistance. Ohm's Law, Power, and Energy. Series Circuits. Parallel Circuits. Series-Parallel Networks. Methods of Analysis and Selected Topics (dc). Network Theorems. Capacitors. Magnetic Circuits. Inductors. Sinusoidal Alternating Waveforms. The Basic Elements and Phasors. Series and Parallel ac Circuits. Series-Parallel ac Networks. Methods of Analysis and Selected Topics (ac). Network Theorems (ac). Power (ac). Resonance. Decibels, Filters, and Bode Plots. Pulse Waveforms and the -R-C Response. Polyphase Systems. Nonsinusoidal Circuits. Transformers. System Analysis—An Introduction.